Finding Fitting Solutions to Assessment of Indigenous Young Children’s Learning and Development: Do It in a Good Way - Ball, Jessica (Frontiers in Education, 2021)
Standardized, norm-referenced assessments of young children’s learning and development pose a number of challenges when used with Indigenous children, beginning with the very notion of the construct “early childhood” that runs counter to some Indigenous ways of knowing and being. Indigenous community leaders and knowledge keepers reject the idea that all children should develop according to a homogenizing universal standard that is not grounded in specific culturally based goals and practices surrounding children’s development and does not respect each child’s unique character. Three key problems arise with creating appropriate assessment of Indigenous young children’s learning and development: 1) assessment in early childhood programs is often done from the perspective of whether children are on track to be ready for school; 2) school systems, early childhood programs, and practitioners face a barrage of pressure to measure children’s “progress” against universalist norms derived from Euro-Western ways of knowing and goals for children’s development; and 3) knowledge of diverse Indigenous young children’s varied lived experiences in today’s urban and rural communities is extremely limited. This paper discusses these obstacles and draws from the author’s many years of collaborating with Indigenous children, families, and communities to co-create culturally relevant assessment in a good way.